Demand Theory without a Utility Index–A Comment - Newman, P. K.; Read, R. C. (Review of Economic Studies, 1958)
P. K. Newman, R. C. Read; Demand Theory without a Utility Index—A Comment, The Review of Economic Studies, Volume 25, Issue 3, 1 June 1958, Pages 197–199,